2019
DOI: 10.1021/acs.jced.9b00100
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Vapor–Liquid Equilibrium Measurements for the Pentan-2-one + Propan-1-ol/Butan-1-ol System within 342–363 K

Abstract: The aim of this work was to measure and model highprecision isothermal binary vapor−liquid equilibrium (VLE) phase data for the pentan-2-one + propan-1-ol/butan-1-ol system to aid in the separation process design. P−T−x−y equilibrium measurements were obtained for the pentan-2-one + propan-1-ol system at 342.34, 352.05, and 361.65 K and for the pentan-2-one + butan-1-ol system at 342. 95, 352.65, and 362.55 K at subatmospheric pressures. The data were successfully modeled using the γ−Φ approach by employing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…On the other hand, prop-2-en-1-ol–hexan-2-ol and prop-2-en-1-ol–4-methyl-pentan-2-ol showed a similar point of inflection at x 1 ≈ 0.2 with asymmetric activity coefficient plots, indicating that one of the components had a very low deviation from ideal behavior, supposedly the long-chain secondary alcohol. This asymmetric behavior was also evidenced for pentan-2-one/propanol, water/2-methylpyridine, and water/butane-2,3-diol systems. …”
Section: Resultsmentioning
confidence: 60%
“…On the other hand, prop-2-en-1-ol–hexan-2-ol and prop-2-en-1-ol–4-methyl-pentan-2-ol showed a similar point of inflection at x 1 ≈ 0.2 with asymmetric activity coefficient plots, indicating that one of the components had a very low deviation from ideal behavior, supposedly the long-chain secondary alcohol. This asymmetric behavior was also evidenced for pentan-2-one/propanol, water/2-methylpyridine, and water/butane-2,3-diol systems. …”
Section: Resultsmentioning
confidence: 60%
“…The equilibrium still described by Joseph et al was used for the measurements and a schematic is shown in Figure . The apparatus and operating procedure have been described in detail in previous reported work. The pressure in the still was measured using a WIKA P-10 transducer (0 to 101.3 kPa) calibrated against a WIKA CPH 6000. The reported uncertainty by the manufacturer on the P-10 transducer is 0.05% of full-scale.…”
Section: Methodsmentioning
confidence: 99%
“…Schematic of the apparatus of Joseph et al used in this work (as shown in ref ). 1, Equilibrium chamber; 2, Liquid sampling port; 3, Temperature measurement; 4, Boiling chamber; 5, Variable heat supply to boiler; 6, Heater cartridge and sleeve; 7, Magnetic stirrer and bead; 8, Boiler drain valve; 9, Condensate drain valve; 10, Vapor condensate sampling point; 11, Condenser; 12, Coolant line to condenser; 13, Coolant bath and controller; 14, Chiller; 15, Pressure measurement; 16, Isolation valves; 17, Ballast tank; 18, Cold trap; 19, Vacuum pump.…”
Section: Methodsmentioning
confidence: 99%
“…Schematic of the apparatus of Joseph et al used in this work, as shown in Mavalal et al (1) Equilibrium chamber. (2) Liquid sampling port.…”
Section: Methodsmentioning
confidence: 99%